Dynamic Attachment of Chlorovirus PBCV-1 to Chlorella variabilis - Agarkova, Irina (Virology, 2014)
Chloroviruses infect their hosts by specifically binding to and degrading the cell wall of their algal hosts at the site of attachment, using an intrinsic digesting enzyme(s). Chlorovirus PBCV-1 stored as a lysate survived longer than virus alone, suggesting virus attachment to cellular debris may be reversible. Ghost cells (algal cells extracted with methanol) were used as a model to study reversibility of PBCV-1 attachment because ghost cells are as susceptible to attachment and wall digestion as are live cells. Reversibility of attachment to ghost cells was examined by releasing attached virions with a cell wall degrading enzyme extract. The majority of the released virions retained infectivity even after re-incubating the released virions with ghost cells two times. Thus the chloroviruses appear to have a dynamic attachment strategy that may be beneficial in indigenous environments where cell wall debris can act as a refuge until appropriate host cells are available.